Seroprevalence of melioidosis and its association with blood profiles and pathogens in sheltered dogs in southern Thailand - Punpichaya Fungwithaya; Worakan Boonhoh; Narin Sontigun; Orachun Hayakijkosol; Wiyada Kwanhian Klangbud; Tuempong Wongtawan (Veterinary World, 2024)
Background and Aims: Melioidosis is a notable zoonotic disease in Thailand that can affect both humans and animals. Although dogs are one of the most popular pets worldwide, there is a remarkable lack of information on the prevalence and knowledge of canine melioidosis. This study aimed to estimate the seroprevalence of melioidosis in sheltered dogs and its relationship with the blood profile and blood pathogens. Materials and Methods: ) were diagnosed using conventional polymerase chain reaction. Results: The seroprevalence rates of canine melioidosis and blood pathogen infection were 5.77% (9/156) and 50.64% (79/156), respectively. Seropositive dogs generally have higher lymphocyte counts and aspartate aminotransferase levels but lower total white blood cell, neutrophil, and platelet (PLT) counts than seronegative dogs. No statistically significant difference (p > 0.05) was observed between the seropositive and seronegative dogs' hematology and serum biochemistry findings. Neither the correlation between melioidosis and blood pathogen infection nor the association between melioidosis and thrombocytopenia was statistically significant (p > 0.05). Remarkably, dogs that had coinfections with both melioidosis and blood pathogens demonstrated a significantly reduced PLTcount (49,167 ± 7,167) compared with dogs that tested positive for melioidosis but negative for blood pathogens (139,333 ± 29,913) (p < 0.01). Conclusion: In southern Thailand, the prevalence of canine melioidosis was low but the prevalence of blood pathogens was high. Coinfection with blood pathogens can significantly reduce PLT counts, which may have a potentially serious impact. Future research should focus on conducting seroprevalence studies in the general dog population.
Keywords: Burkholderia infections and melioidosis; Brucella: diagnosis, epidemiology, treatment; Bartonella species infections research